The spider genus Austrochilus Gertsch & Zapfe, 1955 (Araneae: Austrochilidae)—a new species from Chile and a documentation of the male genitalia of austrochilines - Michalik, Peter; Wunderlich, Joerg (Zootaxa, 2017)
The spider genus Austrochilus comprises only six species known from Chile and Argentina. Here, we describe a new species, Austrochilus parwis sp. n., based on a single male and several females. The new species was found in Chile (Region IX) and, based on characters in the male and female genitalia, seems to be closely related to A. forsteri Grismado, Lopardo & Platnick, 2003. The female genitalia were investigated using X-ray microscopy, revealing for the first time the internal organization of austrochiline female genitalia. Furthermore, we provide a comparative documentation of the male genitalia of austrochilines based mainly on type material, and comment on the recently proposed nomenclatorial changes to the family name Austrochilidae.